Capital Investments Plan for 288 Streets from Cluj-Napoca - Paul ZAI; Adrian Mihai INCEU; Dan Tudor LAZĂR (Transylvanian Review of Administrative Sciences, 2006)
This study critically analyzes how the theoretical concept of Capital Investments Plan (CIP) can be employed in order to better understand the financing decisions regarding various investment project undertaken by the Cluj-Napoca City Hall. Different financing scenarios are then analyzed.